Optimisation of xenon-rich stopped-flow spin-exchange optical pumping for functional lung imaging - Skinner, J.G. (2017)
Spin-exchange optical pumping (SEOP) is a hyperpolarisation method used in the hyperpolarisation of noble gases and can enhance nuclear spin polarisation by five orders of magnitude. Hyperpolarised (HP) 129-Xe has many properties that make it ideally suited to clinical lung imaging, but since its first demonstration in animals in 1994 and humans in 1996, translation to the clinic has been hampered by challenges associated with scaling up production.